2020
DOI: 10.1038/s41598-020-77119-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential miRNA biomarkers for the diagnosis and prognosis of esophageal cancer detected by a novel absolute quantitative RT-qPCR method

Abstract: AbstractmiRNAs are expected to become potential biomarkers in the diagnosis and prognosis of Esophageal cancer (EC). Through a series of screening, miR-34a-5p, miR-148a-3p and miR-181a-5p were selected as EC-associated miRNAs. Based on AllGlo probe, a novel absolute quantitative RT-qPCR method with high sensitivity, specificity and accuracy was established for detecting miRNAs. Then the clinical significance of these 3 miRNAs was explored with 213 patients (166 cases with EC and 47 cases with benign diseases) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…miRNAs are a type of highly conserved small noncoding RNA; these small molecules are crucial players in regulating biological processes. 12,25 The abnormal expression of miRNAs is strongly associated with cancer progression. For instance, miR-101 restrains CRC cell migration by regulating EZH2.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are a type of highly conserved small noncoding RNA; these small molecules are crucial players in regulating biological processes. 12,25 The abnormal expression of miRNAs is strongly associated with cancer progression. For instance, miR-101 restrains CRC cell migration by regulating EZH2.…”
Section: Discussionmentioning
confidence: 99%
“…As diagnostic tools, miRNAs have been proved to be detectable in formalin-fixed paraffin-embedded (FFPE) specimens, in fine needle aspiration biopsies (FNABs) and in various body fluids, such as plasma, saliva, and urine [ 167 , 168 ]. In this context, it was shown that the level of miR-34a-5p increased, while miR-148a-3p and miR-181a-5p decreased in blood samples of patients with EC when compared with controls; moreover, miR-181a-5p was proposed as a biomarker for early EC [ 169 ]. MiR-21 and miR-375 also were tested for their diagnostic potential in EC in two different studies; miR-21 was found to be up-regulated in serum samples from patients with EC, while miR-375 was found to be down-regulated.…”
Section: Future Perspectives: Liquid Biopsy Drug Resistance and mentioning
confidence: 99%
“…It is widely acknowledged that miRNAs act as mediators of anti-cancer drug sensitivity [ 169 ], so it is not surprising that many microRNAs have been proposed as biomarkers for response to therapy in various malignancies, among which EC is no exception. Table 3 outlines some examples of microRNAs whose expression was linked with response to various anti-cancer therapies.…”
Section: Future Perspectives: Liquid Biopsy Drug Resistance and mentioning
confidence: 99%
“…The conclusion of this finding was that miR-339-5p can be used to predict the pathological response to preoperative radiotherapy in locally advanced esophageal squamous cell carcinoma, suggesting that it could be a promising noninvasive biomarker for facilitating personalized treatment. Recently, two reports were published concerning the usefulness of a new detection method of miRNA for diagnosis [53,54]. One is a novel absolute qPCR method that uses the AllGlo probe and exhibits a high application value in detecting miRNAs; the other is a combination of circulating miRNA and miRNA isoforms, referred to as isomiR, that is detected by next-generation sequencing.…”
Section: Esophageal Cancermentioning
confidence: 99%